Terminated interventional trials in the clinical trial registry of India database: an analysis to evaluate the reasons for termination - Dutta, Siddhartha; Kaur, Rimplejeet; Haque, Mainul; Bhardwaj, Pankaj; Saxena, Deepak; A. Rahman, Nor Azlina; Lugova, Halyna; Jahan, Dilshad; Islam, Salequl; Chowdhury, Tajkera; Charan, Jaykaran (Dovepress, 2020)
Background: Clinical Trial Registry - India (CTRI) is a valuable tool to access information regarding clinical trials conducted in India. To serve this purpose, the information provided on it must be complete and accurate. The present study was designed to assess the reasons for premature termination of clinical trials on the CTRI database and determine the average timings related to updating information on CTRI. Methods: The data were extracted from the website of Clinical Trial Registry - India; all the terminated trials from 20 July 2007 to 18 December 2019 were included. The reasons given for termination were categorized as scientific reasons, nonscientific reasons, and unspecified reasons. Results: Of 16,579 interventional clinical trials, 243 trials were terminated. Out of these 243 trials, reasons were given in 50 (20.58%). In reasoning with scientific data, the most common reason was safety issues (14%), and among nonscientific data, a significant delay in recruitment was a principal reason (16%). The median time from date of registration to date of modification was 1034 days (0–3912), and the median time from the date of last revision to the date of our analysis was 1329 days (2–3138). Conclusion: The reasons for termination are not mentioned adequately for the terminated clinical trials in the Clinical Trial Registry of India. Efforts need to be done to motivate investigators to report the reasons for termination. Proper planning of trial before initiation may prevent premature termination of clinical trials and ensure fair use of resources.